2009
DOI: 10.4049/jimmunol.0901247
|View full text |Cite
|
Sign up to set email alerts
|

A2A Adenosine Receptor May Allow Expansion of T Cells Lacking Effector Functions in Extracellular Adenosine-Rich Microenvironments

Abstract: Immunosuppressive signaling via the A2A adenosine receptor (A2AR) provokes a mechanism that protects inflamed tissues from excessive damage by immune cells. This mechanism is desirable not only for preventing uncontrolled tissue destruction by overactive immune responses, but also for protecting tumor tissues from antitumor immune responses. In aforementioned circumstances, T cell priming may occur in an environment containing high concentrations of extracellular adenosine. To examine qualitative changes in T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
136
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(145 citation statements)
references
References 68 publications
5
136
0
Order By: Relevance
“…Adenosine strongly impairs development of effector T cells, especially those that produce IFN-γ and are cytotoxic to tumor cells [84]. Sun et al reported that hypoxia can induce T-cell apoptosis through adenosine/adenosine (2) receptor signaling in vitro [85].…”
Section: Immunosuppression After Anti-vegf Therapy By Increased Tumormentioning
confidence: 99%
“…Adenosine strongly impairs development of effector T cells, especially those that produce IFN-γ and are cytotoxic to tumor cells [84]. Sun et al reported that hypoxia can induce T-cell apoptosis through adenosine/adenosine (2) receptor signaling in vitro [85].…”
Section: Immunosuppression After Anti-vegf Therapy By Increased Tumormentioning
confidence: 99%
“…Activation of A2A receptors during T-cell activation significantly inhibits cytotoxicity and cytokine production (Ohta et al, 2009) and has been reported to inhibit T-cell proliferation (Zhang et al, 2004;Deaglio et al, 2007). T cells activated in the presence of an A2A receptor agonist maintain a suppressed phenotype after removal of the agonist (Ohta et al, 2009). A2A receptor activation in T cells suppresses the development of both Th1 and Th2 immune responses, in vitro and in vivo (Csoka et al, 2008).…”
Section: Adenosine-mediated Immunosuppressionmentioning
confidence: 99%
“…The A2A receptor dominantly regulates T-cell functions and is significantly upregulated upon T-cell activation. Activation of A2A receptors during T-cell activation significantly inhibits cytotoxicity and cytokine production (Ohta et al, 2009) and has been reported to inhibit T-cell proliferation (Zhang et al, 2004;Deaglio et al, 2007). T cells activated in the presence of an A2A receptor agonist maintain a suppressed phenotype after removal of the agonist (Ohta et al, 2009).…”
Section: Adenosine-mediated Immunosuppressionmentioning
confidence: 99%
“…The accumulation of extracellular adenosine in tumors generates an immunosuppressive microenvironment that effectively enhances tumor immune escape. Activation of A2A adenosine receptors on T cells has been shown to inhibit T-cell-mediated cytotoxicity, cytokine production (10) and T-cell proliferation (11,12) and to promote T-cell anergy (13).…”
Section: Introductionmentioning
confidence: 99%